Reduction of methane emissions through in-cylinder methods on a lean-burn four-stroke natural gas engine - Bayer, Justin, author; Olsen, Daniel, advisor; Windom, Bret, committee member; Carlson, Kenneth, committee member (Colorado State University. Libraries, 2023)
The U.S. utilizes over 27 trillion cubic feet of natural gas per year for a wide range of uses, including heating and electricity production, according to the U.S. Energy Information Administration. Natural gas (NG) engines used to compress natural gas and generate electricity account for nearly one-quarter of the total methane emissions in the gathering and boosting sector. These methane emissions are referred to as fuel (methane) slip since they originate from the engine fuel supply and result from incomplete combustion. The primary mechanism leading to unburned methane is related to the engine crevice volume. The crevice volume is the region between the side of the piston and the cylinder wall. This region is particularly difficult for the flame to propagate into because the gap is generally smaller than the quench distance. This research evaluates multiple in-cylinder methods to attempt to reduce the methane slip. One of the mitigation strategies is hydrogen blending with the engine's natural gas fuel supply as a means of methane reduction. Converge Computational Fluid Dynamics (CFD) and a Caterpillar G3516J model are implemented to analyze the effects of hydrogen blending. The G3516J engine is a lean-burn engine commonly used for gas compression in the US NG pipeline system. Converge CFD is a solver that couples combustion chemistry and adaptive mesh refinement to model combustion accurately. Simulations of combustion with NG-hydrogen blended fuel are performed with constant fuel energy, achieved by adjusting boost pressure at a constant equivalence ratio. Combustion cycle simulations are performed at various hydrogen blending levels, and the methane emissions are evaluated at the end of the cycle and compared. In addition, the fuel mixtures' pressure is adjusted to reflect similar indicated power and a similar emission comparison is made. The second mitigation strategy that is explored is induced autoignition. This strategy involved advancing the engine's spark timing to hopefully increase the temperature and pressure in the cylinder to have the end-gas auto-ignite and thus burn more fuel that would otherwise become methane slip. This research also incorporates installing a G3516J engine at the Engines and Energies Conversion Laboratory. Advancing the spark timing in the simulations did not show signs of end gas auto-ignition. Although this is the case, the advanced spark timing showed a decrease in unburned methane compared to the baseline. The spark timing with the lowest unburned CH4 percentage decreases from 3.00% to 2.26% by advancing the spark timing by ten crank angle degrees. The hydrogen blending also showed lower unburned CH4 percentages compared to the baseline. After adjusting the simulations to match indicated power output, the lowest results decreased the unburned percentage from 3.00% to 1.20%. NOx emissions were increased by 129% compared to the baseline in the most extreme simulation case. Leaning the fuel mixture lowered the NOx emissions to within 6% of the baseline while still lowering the unburned percentage from 3.00% to 2.67%.
Keywords: emissions; methane; hydrogen; CFD